Optimization of HER3 expression imaging using affibody molecules: Influence of chelator for labeling with indium-111 - Rinne, Sara S. (Sci Rep, 2019)
Radionuclide molecular imaging of human epidermal growth factor receptor 3 (HER3) expression using affibody molecules could be used for patient stratification for HER3-targeted cancer therapeutics. We hypothesized that the properties of HER3-targeting affibody molecules might be improved through modification of the radiometal-chelator complex. Macrocyclic chelators NOTA (1,4,7-triazacyclononane-N,N′,N′′-triacetic acid), NODAGA (1-(1,3-carboxypropyl)-4,7-carboxymethyl-1,4,7-triazacyclononane), DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid), and DOTAGA (1,4,7,10-tetraazacyclododececane,1-(glutaric acid)−4,7,10-triacetic acid) were conjugated to the C-terminus of anti-HER3 affibody molecule Z(08698) and conjugates were labeled with indium-111. All conjugates bound specifically and with picomolar affinity to HER3 in vitro. In mice bearing HER3-expressing xenografts, no significant difference in tumor uptake between the conjugates was observed. Presence of the negatively charged (111)In-DOTAGA-complex resulted in the lowest hepatic uptake and the highest tumor-to-liver ratio. In conclusion, the choice of chelator influences the biodistribution of indium-111 labeled anti-HER3 affibody molecules. Hepatic uptake of anti-HER3 affibody molecules could be reduced by the increase of negative charge of the radiometal-chelator complex on the C-terminus without significantly influencing the tumor uptake.